(untitled) (Itinera, 2017)
Smell indeed is rarely stimulated on modern stages, but when it is, the staging is remembered all the more vividly since the memory of smell lasts longer than other memories. In adaptation of Pereira prétend, Didier Bezace produces odours which also stimulate tastes, such as lemon, sardines and cigars. This article studies the way the different senses are used in Bezace’s staging in order to understand their role, meaning and impact. The article focuses on Didier Bezace’s choice to utilize smell which has a strong symbolical impact enabling the audience to achieve a full process of identification therefore leading them to question their own relationship to History.